2010
DOI: 10.1016/j.jmb.2010.08.055
|View full text |Cite
|
Sign up to set email alerts
|

α-Actinin Is Required for the Proper Assembly of Z-Disk/Focal-Adhesion-Like Structures and for Efficient Locomotion in Caenorhabditis elegans

Abstract: The actin binding protein α-actinin is a major component of focal adhesions found in vertebrate cells and of the focal adhesion-like structures found the body wall muscle of the nematode Caenorhabditis elegans. To study its in vivo function in this genetic model system we isolated a strain carrying a deletion of the single C. elegans α-actinin gene. We assessed the cytological organization of other C. elegans focal adhesion proteins, and the ultrastructure of the mutant. The mutant does not have normal dense b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…We used Bristol N2 as the wild-type strain and the following mutant strains: atn-1(ok84) (obtained from Dr. Bob Barstead; (Moulder et al, 2010)), unc-98(sf19) [Mercer et al, 2003], unc-54(s74) [Moerman et al, 1982] and unc-94(sf20) [Stevenson et al, 2007]. N2 (Bristol) and unc-54(s74) were obtained from the Caenorhabditis Genetics Center.…”
Section: Methodsmentioning
confidence: 99%
“…We used Bristol N2 as the wild-type strain and the following mutant strains: atn-1(ok84) (obtained from Dr. Bob Barstead; (Moulder et al, 2010)), unc-98(sf19) [Mercer et al, 2003], unc-54(s74) [Moerman et al, 1982] and unc-94(sf20) [Stevenson et al, 2007]. N2 (Bristol) and unc-54(s74) were obtained from the Caenorhabditis Genetics Center.…”
Section: Methodsmentioning
confidence: 99%
“…All of these proteins are known or suspected to be located at dense bodies or I-bands, and most are known or suspected to function with α-actinin. α-actinin, a well studied F-actin crosslinking protein, is a major component of nematode dense bodies and vertebrate muscle Z disks [33,17]. …”
Section: Resultsmentioning
confidence: 99%
“…atn-1(ok84) null mutants have abnormally short and broad dense bodies and yet display normal movement on an agar surface by casual observation, and normal swimming in liquid. In contrast, our assay showed that this mutant has a reduced ability to bend as compared to wild type [17]. The bending aspect of locomotion was restored to wild type levels in mutant animals carrying integrated copies of the wild type atn-1 gene.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…54,55 These types of screens resulting in adult Unc genes have probably been saturated and as noted above total 40 genes. However, semiautomated and high-throughput methods for screening adults for mutants having abnormal localization of GFP-tagged proteins 56 that may in the future use "computer vision" for pattern recognition, and newer methods for assessing nematode motility 57,58 open the door to identifying additional mutant genes in the future.…”
Section: Strength Of C Elegans As a Model Genetic Systemmentioning
confidence: 99%